Factors Driving Learner Success in Online Professional Development - Vu, Phu; Cao, Vien; Vu, Lan; Cepero, Jude (International Review of Research in Open and Distributed Learning, 2014)
This study examined factors that contributed to the success of online learners in an online professional development course. Research instruments included an online survey and learners’ activity logs in an online professional development course for 512 in-service teachers. The findings showed that there were several factors affecting online learners’ success in online professional development. In addition, there were also significant differences between successful and unsuccessful online learners in terms of course login frequency and learning activities viewed.